Ethical Dilemmas in Postnatal Treatment of Severe Congenital Hydrocephalus - Wilkinson, Dominic (Cambridge quarterly of healthcare ethics, 2016)
Severe congenital hydrocephalus manifests as accumulation of a large amount of excess fluid in the brain. It is a paradigmatic example of a condition in which diagnosis is relatively straightforward and long-term survival is usually associated with severe disability. It might be thought that, should parents agree, palliative care and limitation of treatment would be clearly permissible on the basis of the best interests of the infant. However, severe congenital hydrocephalus illustrates some of the neuroethical challenges in pediatrics. The permissibility of withholding or withdrawing treatment is limited by uncertainty in prognosis and the possibility of “palliative harm.” Conversely, although there are some situations in which treatment is contrary to the interests of the child, or unreasonable on the grounds of limited resources, acute surgical treatment of hydrocephalus rarely falls into that category.